2014
DOI: 10.1371/journal.pone.0107114
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Meta-Analysis of the Functional Traits of Clonal Plants Foraging in Changing Environments

Abstract: Foraging behavior, one of the adaptive strategies of clonal plants, has stimulated a tremendous amount of research. However, it is a matter of debate whether there is any general pattern in the foraging traits (functional traits related to foraging behavior) of clonal plants in response to diverse environments. We collected data from 97 published papers concerning the relationships between foraging traits (e.g., spacer length, specific spacer length, branch intensity and branch angle) of clonal plants and esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Environmental heterogeneity is considered to favour clonal growth because stoloniferous clonal plants can display a variety of clonal functional traits that allow them to cope with environmental heterogeneity42. Clonal functional traits such as foraging behaviour, clonal integration and spatial division of labour are expected to benefit the performance of clonal plants in heterogeneous environments because they facilitate the exploitation of benign resources, internal exchange of resources and spread of risk91011.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental heterogeneity is considered to favour clonal growth because stoloniferous clonal plants can display a variety of clonal functional traits that allow them to cope with environmental heterogeneity42. Clonal functional traits such as foraging behaviour, clonal integration and spatial division of labour are expected to benefit the performance of clonal plants in heterogeneous environments because they facilitate the exploitation of benign resources, internal exchange of resources and spread of risk91011.…”
Section: Discussionmentioning
confidence: 99%
“…These abilities promote plants to explore and share nutrients under resource limitation. There are three hypotheses addressing this task: (a) clonal plants may actively forage for nutrients in heterogeneous soils by placing ramets preferentially in nutrient‐rich patches (He, Alpert, Yu, Zhang, & Dong, ; Xie, Song, Zhang, Pan, & Dong, ); (b) clonal plants can transport and relocate limiting resources from ramets growing in more benign (e.g., richer) patches to ramets found in more stressful (e.g., poorer) places through clonal spacers (Derner & Briske, ; Stuefer, ; Yu, Wang, He, Chu, & Dong, ); and (c) clonal plants harvest limiting soil resources over larger areas than nonclonal plants thanks to connections between their perennial rhizome and root systems (Jónsdóttir & Watson, ). In addition, clonal and nonclonal plants differ in their fine root architecture (Šmilauerová & Šmilauer, ) and growth plasticity (Weiser, Koubek, & Herben, ).…”
Section: The Compartment‐based Approachmentioning
confidence: 99%
“…When the study set up experiments on several treatment levels, each “treatment level” was paired with “control” to calculated effect size firstly and would be pooled later. Resource treatments (light intensity, nutrient level and water availability) used in the studies followed the explanation in Xie et al ( 2014 ). All data were extracted from tables or digitized from graphs with the software GetData v2.22 ( http://www.getdata-graph-digitizer.com ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we considered ramet biomass as a measure of resource allocated to vegetative growth, and further divided into two parts: aboveground part (shoot, leaf, and stem) and belowground part (root). Because some studies found that stolons and rhizomes have partly different functions (Dong and de Kroon, 1994 ) and because rhizomatous plants are less plastic than stoloniferous plants in response to changes in resource availability (Dong and de Kroon, 1994 ; de Kroon and Hutchings, 1995 ; Xie et al, 2014 ), we considered that biomass allocated to reproduction consisted of two parts: biomass allocated to clonal reproduction (rhizomes or stolons) and biomass allocated to sexual reproduction (flowers, seeds, and fruits; Table 1 ). Additionally, we analyzed the allocation patterns from two perspectives: absolute and relative biomass (Reekie and Bazzaz, 1987 ).…”
Section: Introductionmentioning
confidence: 99%